Heterometallic coordination polymers: Treatment activity on diabetic foot by reducing the excess inflammatory response in the plantar tissue. Issue 1 (January 2021) - Wang, Hai-Yan; Weng, Li; Yang, Hong-Yan; Yang, Xi; Dong, Xiao-Ling; Tan, Xiao-Mei; Wang, Yan
Two new heterometallic coordination polymers formulated as {[LaCo(2.5-pydc)2 (H2 O)4 ]Cl·4H2 O}n (1, 2, 5-H2 pydc = pyridine-2, 5-dicarboxylic acid) and {[LaCo2 Cl3 (4, 4′-bpdc)2 (H2 O)3 ]·H2 O}n (2, 4, 4′-H2 bpdc = 2, 2′-bipyridyl-4, 4′-dicarboxylic acid) have been solvothermally synthesized using the coordination between rare earth/transition metal ions and pyridinedicarboxylic acids. To develop new candidates for enhancing the therapeutic effect of improved negative pressure suction for diabetic foot, the activities of compounds1 and2 were studied. First, the ELISA (enzyme linked immunosorbent assay) detection kit was used and the inflammatory cytokines in the plantar tissue were measured. Besides, the TLR-4-NF-κB signaling pathway was measured with real-time reverse transcription-polymerase chain reaction.